The Impact of Social Media Use on Social Interaction of Students of The Faculty of Medicine, Jenderal Soedirman University - Henny Sutikno; Abdul Basit (Lafadz Jaya Publisher, 2023)
Social media is an internet-based group application that builds on the basis ofideologues and web 2.0 technologies and enables the creation and conversion of content from users that produces both positive and negative impacts. The research method uses qualitative methods and descriptive approaches with informant sources of Jenderal Soedirman University students, Faculty of Medicine. The result of this study is that the use of social media has a complex impact on students' social interactions. While social media can improve connectedness and access to information, its excessive or unbalanced use can interfere with face-to-face communication and mental health. Students need to understand and manage their use of social media wisely, while still appreciating the importance of in-person social interaction and real-world relationship building.